Synaptic structural protein dysfunction leads to altered excitation inhibition ratios in models of autism spectrum disorder. (January 2019) - Howell, Brian W.; Smith, Kathleen M.
Abstract: Genetics is believed to play a key role in the development of Autism Spectrum Disorder (ASD) and a plethora of potential candidate genes have been identified by genetic characterization of patients, their family members and controls. To make sense of this information investigators have searched for common pathways and downstream properties of neural networks that are regulated by these genes. For instance, several candidate genes encode synaptic proteins, and one hypothesis that has emerged is that disruption of the synaptic excitation and inhibition (E/I) balance would destabilize neural processing and lead to ASD phenotypes. Some compelling evidence for this has come from the analyses of mouse and culture models with defects in synaptic structural proteins, which influence several aspects of synapse biology and is the subject of this review. Remaining challenges include identifying the specifics that distinguish ASD from other psychiatric diseases and designing more direct tests of the E/I balance hypothesis.